Educational Value of Tri Hita Karana's in Garap Gending Sidhakarya Mask Dance - putra, I wayan agus suardiana; Widodo, Widodo; Wadiyo, Wadiyo (Catharsis, 2020)
This study aims to analyze the educational value of Tri Hita Karana (harmonization of humans with humans, harmonization of humans with nature, and harmonization of humans with God) which represents the musical composition of the Sidhakarya Mask dance at the odalan ceremony in Pura Agung Giri Natha Semarang. This study used qualitative analytic method with interdisciplinary approach of ilmusosiology and education. The data was obtained by using observation, interview, and document study techniques. The data analysis technique used intrinsic and extrinsic analysis techniques, and the data were analyzed with the stages of data reduction, data classification, and data display. The validity of the data used the credibility test (internal validity), transferability (external validity), dependability (reliability), and confirmability (objectivity). The results of this study indicate that the garap material represents the educational value on the harmonization of humans with God which was produced from the gending notes of the Sidhakarya Mask Dance; 1) the educational value of harmonization of humans with nature was represented when the penabuh of the Seni Puspa Giri Studio are able to control the five senses and there is happiness in the penabuh, and the form of the yadya offering is in the form of its performance when the odalan ceremony shows a sense of devotion and the harmonious relationship between humans with God; 2) the educational value on the harmonization of humans with nature was represented when the penabuh of the Seni Puspa Giri Studio played the notes in the Gong Kebyar gamelan, there are vibrations of sound that are the same as sounds produced by nature (the sound of space, water, land, and Earth) which are suitable and create harmony; 3) the educational value of harmonization between humans with humans was represented when the penabuh of Ugal hinted hard and soft of the gending sound, the Kendang performer told another Kendang performer when he forgot with the playing motive of Kendang, when the Kendang performer told the Kajar perfromer that the way of playing was wrong, so the penabuh played together the gending of Sidhakarya Mask dance which proved that the value of human with harmonization. The results of this study can be used as a reference regarding the educational value of Tri Hita Karana which was represented in the garap of gending. Kata Kunci: garap, gending tari Topeng Sidhakarya, nilai pendidikan Tri Hita Karana, upacara odalan.